Sliding‐mode variable structure controller for cascade STATic var COMpensator. Issue 2 (1st February 2013) - Wu, Junyong; Chen, Qichao; Du, Mingjun; Yu, Shuqin
Abstract : The authors propose a novel sliding‐mode variable structure controller for cascade STATic var COMpensator (STATCOM), which integrates the direct feedback linearisation control for the balanced system and the individual phase instantaneous current tracking control for the unbalanced system, to achieve a versatile STATCOM controller. It can adapt automatically to various distribution system conditions. Based on the degree of system unbalance, the authors design a switching function to make the STATCOM work reliably with satisfactory performance, when the serious voltage sag occurs or the distribution system enters serious asymmetrical condition. The authors also propose a hierarchical DC‐link voltages balance control strategy. The authors build a detailed ± 10 MVar STATCOM model with power system CAD and electro magnetic transient in DC system (PSCAD/EMTDC) and validate the effectiveness and advantage of the proposed control strategy with the simulation study.